PENERAPAN METODE SAM’IYAH SYAFAWIYAH BERBANTUAN MEDIA CERITA BERGAMBAR UNTUK MENINGKATKAN KETERAMPILAN MEMBACA DI KELAS V MADRASAH IBTIDAIYYAH HIDAYATUL MUBTADIIN SRIKATON PRINGSEWU - Sholikhatun, Amelia; Zuliana, Erni; Zulhannan, Zulhannan; Nur Mizan, Ahmad (Penerbit Lafadz Jaya, 2026)
This research is motivated by the low reading ability of students as seen from the average score which is still below the Minimum Completion Criteria (KKM). This study aims to improve the Arabic reading skills of fifth grade students of MI Hidayatul Mubtadiin Srikaton Pringsewu through the application of the Sam'iyah Syafawiyah method assisted by picture story media. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles which include the planning stage, action implementation, observation, and reflection. The research subjects numbered 18 students. Data collection techniques were carried out through reading tests, observation, and documentation. The results of the study showed an increase in students' reading skills at each stage. The average score of students in the pre-test stage was 56 with a learning completeness of 39%. In cycle I the average score increased to 65 with a completeness of 56%. In cycle II the average score increased to 87 with a learning completeness of 83%. These results indicate that the application of the Sam'iyah Syafawiyah method assisted by picture story media is effective in improving students' Arabic reading skills.